Science and precaution in interactive risk evaluation - Deblonde, Marian; Barriat, Valérie-Anne; Warrant, Françoise; Goorden, Lieve; Valenduc, Gérard (Brussels, 2005)
"The aim of this research project is to develop guidelines for the organisation of the process of scientific advising. The project intends to contribute to interactive procedures and methods in relation to risk evaluation and management that are both scientific and precautionary. The present proposal offers the opportunity to prepare the involvement of stakeholders and citizens in these interactive processes."